H2O SPECIATION IN FLOAT GLASS AND SODA LIME SILICA GLASS - Stuke A.; Behrens H.; Schmidt B.C.; Dupree R. (My University, 2006)
The speciation of H2O in float glass (FG) and soda lime silica glass (SLS) was investigated using IR and NMR spectroscopy. Molar absorption coefficients for the near-infrared (NIR) combination bands at 4500 and 5200 cm- 1, assigned to OH groups and H2O molecules, respectively, were determined using hydrated glasses containing 0.5-7.4 wt.% of dissolved H2O. Water contents of the samples used in the calibration were determined by Karl-Fischer titration or mid-infrared spectroscopy. Different combinations of baseline corrections and intensity measures were applied to evaluate the NIR spectra with tangent baselines and measurement of peak heights giving the best reproducibility. Deviations up to 30% relative were observed between water species concentrations determined by NIR spectroscopy using an internally consistent calibration based on bulk water content and those determined by low temperature static 1H NMR spectroscopy. This implies that the assumption of constant NIR absorption coefficients may be not valid for glasses in which dissolved water is strongly hydrogen-bonded. Based on the NMR data the NIR absorption coefficients were re-calibrated, demonstrating that in particular the absorption coefficient for the band at 4500 cm- 1 (ε4500) varies with water content. For float glass ε4500 grows by 35% when the water content increases from 0.5 to 4.0 wt.%. An opposite trend was found for soda lime glass with an approximately linear decrease of ε4500 by 27% relative between 0.5 and 7.5 wt.% H2O. For the 5200 cm- 1 band we could not resolve a dependence of the absorption coefficient (ε5200) on water content (values of 0.89 ± 0.06 and 0.95 ± 0.06 L mol- 1 cm- 1 were determined for FG and SLS glass, respectively). However, this may be a consequence of the low precision in determining of ε5200 at water contents below 2 wt.%. Based on the improved NIR calibrations, the OH concentrations at given water content are typically lower in FG than in SLS glasses with apparent saturation values of 1.4 wt.% (FG) and 2.2 wt.% (SLS) of water dissolved as OH groups. The difference in OH contents could be related to the different chemical compositions of these two glasses, in particular the concentration of alkaline-earth elements and the ratio of Mg / Ca, which are larger in FG glass than in SLS glass. Using the new water speciation data, we have re-evaluated the molar absorption coefficient for the H2O bending vibration band at 1630 cm- 1. © 2006 Elsevier B.V. All rights reserved.
Keywords: ABSORPTION COEFFICIENTS; FLOAT GLASS; H2O SPECIATION; IR SPECTROSCOPY; NMR SPECTROSCOPY; SODA LIME SILICA GLASS